HTPB‐Clay Nanocomposites (HCN): An Efficient Burning Rate Catalyst for Composite Propellant. Issue 5 (14th March 2019) - Ghosh, Kavita; Chimurkar, Dhanraj; Kumar, Guddu; Kumar, Arvind; Banerjee, Shaibal; Gupta, Manoj
Abstract: In present study, two types of montmorillonite clay, organically modified with polar and apolar moieties, are used, for preparation of HTPB‐clay nanocomposites (HCN) by dispersion of nanoclay in polymer matrix with high shear mixing. These nanocomposites are evaluated in composite propellants for their catalytic effect on decomposition of ammonium perchlorate a work horse oxidizer. Several composite propellant formulations containing 1–3 weight % of nanoclays over binder, were prepared. Along with this, formulations with conventional burning rate catalyst like iron oxide in 1–3 weight % over binder, and formulation without any burning rate catalyst as base composition were also processed. All these formulations were evaluated by means of theoretical prediction, end of mix viscosity, ballistic properties, mechanical properties, sensitivity parameters and thermophysical properties. Experimental results showed that HCN based compositions have lower or comparable end of mix viscosity than base compositions. Further characterization revealed that formulations with 3 weight % of nanoclays over binder have 70 % higher burning rate than base composition as well as 20–25 % higher burning rate than compositions having 3 weight % of iron oxide over binder. Pressure exponent values are determined for 3 to 11 MPa of pressure range and were found to be significantly higher for HCN based compositions (0.33 to 0.7) in comparison to the base composition. Mechanical properties and sensitivity data of HCN based compositions are comparable with base composition. Thermal studies revealed decrease in onset temperature of decomposition of AP with presence of nanoclay which may be the probable cause for enhancement in burning rate. Abstract :